2019
DOI: 10.1124/dmd.118.085506
|View full text |Cite
|
Sign up to set email alerts
|

Role of ABCG2 in Secretion into Milk of the Anti-Inflammatory Flunixin and Its Main Metabolite: In Vitro-In Vivo Correlation in Mice and Cows

Abstract: Flunixin meglumine is a nonsteroidal anti-inflammatory drug (NSAID) widely used in veterinary medicine. It is indicated to treat inflammatory processes, pain, and pyrexia in farm animals. In addition, it is one of the few NSAIDs approved for use in dairy cows, and consequently gives rise to concern regarding its milk residues. The ABCG2 efflux transporter is induced during lactation in the mammary gland and plays an important role in the secretion of different compounds into milk. Previous reports have demonst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 57 publications
1
16
0
Order By: Relevance
“…4). This difference is similar to the values obtained previously in our group for another substrate belonging to the NSAID family, flunixin [20]. NSAID transport in the mammary gland can have clinical, toxicological and nutritional implications.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…4). This difference is similar to the values obtained previously in our group for another substrate belonging to the NSAID family, flunixin [20]. NSAID transport in the mammary gland can have clinical, toxicological and nutritional implications.…”
Section: Discussionsupporting
confidence: 90%
“…Furthermore, ABCG2 is also involved in the distribution and elimination of diclofenac glucuronides in mice [19]. Recent studies have demonstrated that ABCG2 is involved in the secretion of flunixin and its main metabolite, 5OH-flunixin, into milk [20]. Although meloxicam is a widely used drug in the medical and veterinary field, there are no studies of its interaction with ABC transporters which might influence its drug pharmacokinetics.…”
Section: Introductionmentioning
confidence: 99%
“…Danofloxacin, enrofloxacin and ciprofloxacin are also effluxed into milk by bovine ABCG2 more efficiently in polymorphic Y581S than in wild-type cows [151,152,169]. After administration of flunixin to dairy cows, both the parental drug and its metabolite 5-hydroxyflunixin were secreted into milk and in the case of flunixin, its secretion was increased in carriers of the polymorphism Y581S compared to wild-type cows [141].…”
Section: Polymorphisms In Transporters With Increased Expression Imentioning
confidence: 99%
“…Although some of these drugs, such as diclofenac, are in vitro substrates of ABCG2 [140], there is no information about the specific involvement of this transporter in its secretion into milk. Until now, flunixin and its metabolite 5-hydroxyflunixin are the only NSAIDs which have been shown to be transferred into milk by murine and bovine ABCG2 in vivo [141].…”
Section: Efflux Transporters: Abcsmentioning
confidence: 99%
See 1 more Smart Citation